Systematic review and meta-analysis of prognostic role of splenic vessels infiltration in resectable pancreatic cancer. Issue 1 (January 2018) - Crippa, Stefano; Cirocchi, Roberto; Maisonneuve, Patrick; Partelli, Stefano; Pergolini, Ilaria; Tamburrino, Domenico; Aleotti, Francesca; Reni, Michele; Falconi, Massimo
Abstract: Background: Identification of factors associated with dismal survival after surgery in resectable pancreatic ductal adenocarcinoma is important to select patients for neoadjuvant treatment. The present meta-analysis aimed to compare the results of distal pancreatectomy for resectable adenocarcinoma of the pancreatic body-tail with and without splenic vessels infiltration. Methods: A systematic search was performed of PubMed, Embase and the Cochrane Library in accordance with PRISMA guidelines. The inclusion criteria were studies including patients who underwent distal pancreatectomy for pancreatic cancer with or without splenic vessels infiltration. 5-year overall survival (OS) was the primary outcomes. Meta-analysis was carried out applying time-to-event method. Results: Six articles with 423 patients were analysed. Patients with pathological splenic artery invasion had a worse survival compared with those without infiltration (Hazard ratio 1.76, 95% CI 1.36–2.28; P < 0.0001). A similar results was found when considering pathological splenic vessels infiltration, showing that survival was significantly poorer when splenic vein infiltration was present (Hazard ratio 1.51, 95% CI 1.19–1.93; P = 0.0009). Conclusions: This meta-analysis showed worse survival for patients with splenic vessels infiltration undergoing distal pancreatectomy for pancreatic cancer. Splenic vessels infiltration represents the stigmata of a more aggressive disease, although resectable.